2010
DOI: 10.1007/s12024-009-9120-x
|View full text |Cite
|
Sign up to set email alerts
|

Medicolegal evaluation of suicidal deaths exemplified by the situation in Germany

Abstract: Suicide is a significant form of unnatural death and must be differentiated as such from other violent manners of death (homicide, accident), but also from unexpected deaths due to natural causes. The distinction is made on the basis of a careful collection and correct interpretation of post-mortem forensic findings on the one hand, the general background of the case and the criminal investigation at the scene on the other. For competent assessment by the post-mortem medical examiner and/or forensic pathologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
0
16
0
4
Order By: Relevance
“…Her ne kadar olgumuzun psikiyatrik antesedanı ile ilgili bilgi bulunmamakta ise de bu tarz çoklu yöntemin kullanıldığı intihar olguların-da, önceden var olan kişilik bozukluğu, depresyon, madde kullanımı veya şizofreni gibi psikiyatrik hastalıklara sıklıkla rastlanmaktadır (3,5,16). Bu nedenle de olayın orijini aydınlatılmaya çalışılırken psikiyatrik özgeçmişin sorgulanması; olgunun bu tarz bir ölüm yolunu seçme konusunda risk grubunda olup olmadığını açığa çıkara-bilecektir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Her ne kadar olgumuzun psikiyatrik antesedanı ile ilgili bilgi bulunmamakta ise de bu tarz çoklu yöntemin kullanıldığı intihar olguların-da, önceden var olan kişilik bozukluğu, depresyon, madde kullanımı veya şizofreni gibi psikiyatrik hastalıklara sıklıkla rastlanmaktadır (3,5,16). Bu nedenle de olayın orijini aydınlatılmaya çalışılırken psikiyatrik özgeçmişin sorgulanması; olgunun bu tarz bir ölüm yolunu seçme konusunda risk grubunda olup olmadığını açığa çıkara-bilecektir.…”
Section: Discussionunclassified
“…Olay yerinin/anının yeniden yapılandırılması adı verilen ve olay anında mağdurun, ölenin, failin ve olay yerindeki diğer tüm nesnelerin pozisyonlarının belirlenmesi ve birbirine göre konumlandırılması sürecinin beslendiği disiplinlerden birisi de kan lekesi model analizidir (15,16,20). Sunulan bu olguda da dönüştürülmüş kurusıkı tabanca ateşlendiği anda kişinin pozisyonu hakkında olay orijininin intihar olarak değerlendirilebilmesini sağlayan bilgiler vermiştir.…”
Section: Discussionunclassified
“…According to the suicide notes, it can be assumed that partnership problems were the man's main motive for taking his own life. The blood ethanol concentration of 1.09 per mille indicated that he was under the disinhibiting influence of alcohol (so-called courage dose [11]). In the study material of Blumenthal [2], which comprised 406 suicidal gunshots to the head, a positive blood alcohol concentration (BAC) was seen in 40% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hanging · Mutilation · Sexual asphyxia · Suicide · Forensic medicine henden Sekundärtrauma, etwa bei Sturz durch eine defekte Schlinge bei versuchtem Erhängen [11].…”
Section: Introductionunclassified